Calendar of Events. (Communications of the ACM, 2016)
A calendar of events related to computer software development and computing from December 2016 to February 2017 is presented including the Winter Simulation Conference in Arlington, Virginia, the International Middleware Conference in Trento, Italy, and the Foundations of Genetic Algorithms conference in Copenhagen, Denmark.